2003
DOI: 10.1128/jvi.77.19.10706-10713.2003
|View full text |Cite
|
Sign up to set email alerts
|

Simian Virus 40 T Antigens and J Domains: Analysis of Hsp40 Cochaperone Functions in Escherichia coli

Abstract: The N-terminal exon of DNA tumor virus T antigens represents a J domain that can direct interaction with the host-encoded Hsp70 chaperones. We have taken advantage of rapid Hsp40 cochaperone assays with Escherichia coli to assess simian virus 40 (SV40)-encoded J-domain loss of function. We found a strong correlation between loss of cochaperone function in E. coli and defective SV40 growth, suggesting that the major role of the J domain in DNA tumor viruses is to provide cochaperone function. We also report the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…ST contains an N-terminal J domain, which is an ϳ70-amino-acid, four-helix structure found in DNA J-type molecular chaperones (11,41). J domains function as cochaperones by recruiting and activating the ATPase activity of Hsp70 (heat shock protein 70) proteins (21).…”
Section: Resultsmentioning
confidence: 99%
“…ST contains an N-terminal J domain, which is an ϳ70-amino-acid, four-helix structure found in DNA J-type molecular chaperones (11,41). J domains function as cochaperones by recruiting and activating the ATPase activity of Hsp70 (heat shock protein 70) proteins (21).…”
Section: Resultsmentioning
confidence: 99%
“…There has been little systematic genetic analysis of J domains, even for E. coli DnaJ (17,24,25). To map the DnaJ residues necessary for polyomavirus large T function, we carried out extensive mutagenesis of the J domain.…”
mentioning
confidence: 99%
“…Less is known about the role of the J domain in polyomavirus middle T and small T. Although some mutations in the middle T J domain have been shown to affect transforming ability (11), mutation of the HPD loop was found not to alter the ability of middle T to transform cells (4,26). This suggests that activation of DnaK, the normal role for DnaJ, is not required for transformation.There has been little systematic genetic analysis of J domains, even for E. coli DnaJ (17,24,25). To map the DnaJ…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The particles formed in vitro with VP1 pentamers and HF-VP2 are morphologically irregular, indicating that some other component(s) is required to form completely spherical virions. It has been suggested that proper virus assembly requires chaperones in vivo (35,36). Furthermore, the SV40 minichromosome is also 4 M. Kawano, unpublished observations.…”
Section: Discussionmentioning
confidence: 99%